Yield and yield components of short duration transplant Aus rice (cv. Parija) as influenced by plant spacing and nitrogen level - Paul, Swapan Kumar; Roy, Bithi; Hasan, Ahmed Khairul; Sarkar, Md Abdur Rahman (Fundamental and Applied Agriculture, 2017)
In our country most of the fields remain fallow after Boro harvest and before plantation of T. Aman seedling. Indigenous cultivar Parija rice cultivation is becoming popular in northern region of Bangladesh to ensure food security especially in the off season. So, optimization of agronomic practices for Parija rice cultivation is important. In this regard, an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from April to July 2012 to examine the effect of plant spacing and nitrogen level on the yield performance of short duration transplant Aus rice (cv. Parija). The experiment consisted of four spacing viz. 20 cm × 20 cm, 20 cm × 15 cm, 20 cm × 10 cm and 15 cm × 15 cm and four nitrogen levels viz. 0, 35, 70 and 105 kg N ha-1. The experiment was laid out in a Randomized Complete Block Design with three replications. At harvest the tallest plant (79.39 cm) was recorded at the spacing 20 cm × 10 cm and the shortest one (74.78 cm) from 20 cm × 20 cm. The highest number of total tillers hill-1 (10.08), effective tillers hill-1 (8.31), grains panicle-1 (146.49), grain yield (2.36 t ha-1) and straw yield (2.97 t ha-1) were found at the plant spacing 20 cm × 15 cm. The lowest grain yield (1.97 t ha-1) and straw yield (2.49 t ha-1) were obtained from the spacing of 15 cm × 15 cm. The highest plant height (77.54 cm) at harvest was found by application of 105 kg N ha-1 while the shortest one (73.28 cm) from control plots (without N). The highest number of total tillers hill-1 (11.96), effective tillers hill-1 (10.39), grains panicle-1 (151.10), grain yield (2.95 t ha-1), straw yield (3.58 t ha-1) and harvest index (45.12 %) were found when fertilized with 70 kg N ha-1. The lowest number of effective tillers hill-1 (3.68), grains panicle-1 (133.83), grain yield (0.91 t ha-1), straw yield (1.52 t ha-1) and harvest index 37.65 % were found in control treatment. The highest number of total tillers hill-1 (12.52), grains panicle-1 (157.17), grain yield (3.41 t ha-1) and straw yield (4.05 t ha-1) were recorded at the spacing of 20 cm × 15 cm fertilized with 70 kg N ha-1 while the lowest grain yield (0.68 t ha-1) was obtained from 15 cm × 15 cm spacing with control treatment. It can be concluded that short duration Aus rice (cv. Parija) can be transplanted at the 20 cm × 15 cm spacing with 70 kg N ha-1 to obtain maximum yield.